Hubungan antara Kompensasi dengan Kinerja Guru Sekolah Menengah Pertama Negeri di Kecamatan Kebayoran Baru Kota Administrasi Jakarta Selatan - Charity Anggraeni; Neti Karnati; Diah Armeliza (Program Studi Manajemen Pendidikan, 2016)
This study aims to determine the relationship between compensation and teacher’s job performance of Middle School in Kecamatan Kebayoran Baru, South Jakarta. The method used is descriptive in the form of a survey. The population in this study is a teacher in the Middle School at Kecamatan Kebayoran Baru, South Jakarta. Samples were taken by using proportional random sampling technique. Based on this technique, the sample size used in this study were 69 from 225 teachers. Data collection for compensation (Variable X) and job performance (Variable Y) using a questionnaire. From the results of hypothesis testing to test the significance of the correlation is obtained that tcount 5.421 > ttable 1.670. Thus it can be said that the hypothesis can be accepted. This means that the null hypothesis (H0) is rejected. The results of this study it can be concluded that there is a positive relationship between compensation with teacher’s job performance of Middle School in Kecamatan Kebayoran Baru, South Jakarta. The results of this study also indicate that compensation’s contribution to job performance is compensated at 30.49 %. From these values can be indicated that compensation had a positive effect on teacher’s improvement of job performance.